Development of Learning Teaching Materials Using Picture Book As Acquisition Media Indonesian Language for Students of Grade V SDN 129 Hutarimbaru, East Panyabungan Mandailing - Sahara, Siti; Sutikno (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to 1) describe the acquisition of Indonesian using picture books in elementary school children and 2) describe the development of picture books that are appropriate for the cognitive development of elementary school students. This research is a type of research or what is called research and development (R&D). The sources of research data were teachers, parents, and class V students of SDN 129 Hutarimbaru Kec. East Panyabungan District. Qualitative and quantitative data analysis techniques were used. Results of Indonesian language acquisition for class V children at SDN 129 Hutarimbaru Kec. East Panyabungan District. Mandailing Natal for the 2024-2025 learning year consists of several stages: the pre-linguistic, one-word, two-word, and many-word stages. The development of picture books in research went through information gathering stages, and it was discovered that there were problems in developing children's language acquisition due to limited books and teacher competence in teaching. The next stage was the preparation of the instrument and continued with validation of the instrument that had been prepared. The results showed that the instrument was suitable for use. The next stage was the development of book designs, namely, teachers’ guidebooks and student books. The results of expert validation of the product showed that the average score for the product assessment of teachers’ manuals and student books was 3.98, indicating that the book developed was suitable for use without revision. In the next stage, a product trial was carried out, the result of which was that the teacher's guidebook received a score of 3.93 in the "very good" category and the student's book received a score of 3.96 in the "very good" category. This research produced the final product in the form of a picture book completed with a teacher's guide book for one year, first and second-semester student books